2002
DOI: 10.1002/art.10799
|View full text |Cite
|
Sign up to set email alerts
|

Minor impact of juvenile arthritis on nutritional status in young adult patients

Abstract: Objective. Growth abnormalities and poor nutritional status have been reported in children with juvenile idiopathic arthritis (JIA). The aim of this study was to evaluate the impact of juvenile chronic rheumatic disease on current nutritional status in adult patients in remission or with active disease. Methods. One hundred thirty-eight women and 82 men, aged >20 years, with JIA were studied after a mean disease duration of 15.5 ؎ 2.3 years. Eighty-four (61%) of the women and 49 (60%) of the men were in remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
(16 reference statements)
1
6
0
5
Order By: Relevance
“…Haugen et al [22] compared nutritional status with BC measurements by DXA from 220 individuals aged older than 20 years who had been diagnosed as JIA in childhood and healthy controls. They reported that the final height and BMI of the sample were within normal range, except among women with the systemic subtype and those who had used or were using corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Haugen et al [22] compared nutritional status with BC measurements by DXA from 220 individuals aged older than 20 years who had been diagnosed as JIA in childhood and healthy controls. They reported that the final height and BMI of the sample were within normal range, except among women with the systemic subtype and those who had used or were using corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos observacionais associaram o uso, duração ou dose cumulativa de glicocorticóide com redução na estatura (4,7,12,19,21,22) . A maioria desses estudos não utilizou análise multivariável para ajustar para o efeito de possíveis fatores de viés, como subtipo, duração e severidade da doença (7,19,21,22) .…”
Section: Discussionunclassified
“…Alguns estudos observacionais associaram o uso, duração ou dose cumulativa de glicocorticóide com redução na estatura (4,7,12,19,21,22) . A maioria desses estudos não utilizou análise multivariável para ajustar para o efeito de possíveis fatores de viés, como subtipo, duração e severidade da doença (7,19,21,22) . Zak et al (12) e Garcia-Consuegra Molina et al (4) apresentaram modelos de regressão linear múltipla em que o uso de glicocorticóides foi considerado um fator independente para a redução da estatura ou baixa velocidade de crescimento.…”
Section: Discussionunclassified
See 2 more Smart Citations